I-SPEAK: The Developed Interactive Speech Proficiency Enhancement and Assistance Kit for Oral Communication - Cabantog, Eva Joyce (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to develop and validate a mobile application, I-SPEAK (Interactive Speech Proficiency Enhancement and Assistance Kit), designed to improve the oral communication skills of Grade 11 students. Addressing the persistent challenges in English proficiency and student engagement in Oral Communication, the research responded to the need for innovative, technology-based instructional materials aligned with the MATATAG curriculum agenda. Using the Design and Development research method, the study involved 30 Grade 11 learners from Biñan Integrated National High School and 15 Senior High School Oral Communication teachers and ICT Coordinators from six public schools in the City Schools Division of Biñan. Two Education Program Supervisors served as expert validators. Participants were selected through purposive sampling. The mobile app was assessed using a four-point Likert scale and analyzed through mean scores and an independent samples t-test. Results revealed that I-SPEAK is highly valid in terms of instructional components (objectives, concepts, directions, topics, exercises, and reflections) and highly acceptable in terms of functionality, accuracy, suitability, usability, and efficiency. A statistically significant improvement was found in the learners’ performance as evidenced by increased posttest scores, confirming the app’s effectiveness in enhancing speech proficiency. The study identified several educational values, including motivation, accessibility, innovation, relevance, and learner-centered engagement. In conclusion, I-SPEAK proved to be an effective and accessible tool that addresses the oral communication challenges of Grade 11 students and supports teachers in delivering lessons, especially during disruptions such as class suspensions. This research supports the integration of mobile-based learning tools in the senior high school curriculum to promote critical communication skills and time-on-task efficiency.